The ultimate quick module for workplace writing: perfect for higher learning institution staff: clear, practical, and ready for self-learning! - Mohd Basari, Shahrul Nizam; Ramdzan Ali, Al Amirul Eimer; Mohamad Ali, Afiza; Abdullah, Nur Nabilah; Sahar, Rafidah; Rashid Ali, Farrah Diebaa; Jaraih, Mohd Saifullah (KSTCL Press, 2026)
The Ultimate Quick Module for Workplace Writing is a practical, self-learning resource designed to enhance workplace writing competencies among administrative staff in higher learning institutions. Grounded in the widely accepted 7 Cs of Communication framework, the module systematically covers essential workplace writing formats including emails, formal letters, memorandums, minutes of meeting, and announcements. Each section integrates clear explanations, real-life examples, poor-versus-improved comparisons, structured exercises, and answer keys to facilitate immediate application in professional contexts. Emphasis is placed on clarity, coherence, tone, and reader awareness to strengthen institutional credibility and operational efficiency.